Case Report: Meningioma with unusual extracranial extension to the temple and orbit - Bao, Jing; Xu, Xuxu; Pan, Zhenjiang; Wei, Shepeng (Frontiers in Oncology, 2026)
Meningiomas are the most common primary intracranial tumors, yet extracranial extension occurs in only 1% to 2% of cases and is rarely the initial manifestation. We report a 66-year-old man who presented with a progressively enlarging right frontotemporal subcutaneous mass that had recently accelerated in growth and was initially considered a benign soft tissue lesion. Computed tomography revealed a subcutaneous mass with additional lesions of similar attenuation involving the intracranial and intraorbital compartments. Contrast-enhanced magnetic resonance imaging demonstrated homogeneously enhancing lesions in the subcutaneous temporal tissue, temporalis muscle, orbit, and the floor of the middle cranial fossa, raising concern for a common origin with multicompartment extension. The extracranial component was excised under general anesthesia; the mass was located deep to the temporalis muscle and was removed completely with partial preservation of the muscle. Histopathological examination confirmed a World Health Organization grade I meningothelial meningioma with a Ki-67 labeling index of 10%. Early postoperative CT obtained 1 week after surgery showed expected postoperative changes and confirmed that the intraorbital and middle cranial fossa lesions had not been treated. At telephone follow-up, the patient reported no neurologic or visual symptoms; he had traveled abroad and elected to defer further treatment and surveillance imaging, with plans to re-evaluate after returning in approximately 6 months. This case illustrates an unusual growth pattern of meningioma with simultaneous intracranial, subcutaneous, muscular, and orbital involvement presenting primarily as a temporal mass with minimal neurologic or ophthalmologic symptoms. Comprehensive neuroimaging was essential for diagnosis and mapping of disease extent, and management required balancing surgical accessibility, anticipated control with radiosurgery, and patient preference within a multidisciplinary framework.